2022
DOI: 10.1002/evl3.273
|View full text |Cite
|
Sign up to set email alerts
|

Pollution induces epigenetic effects that are stably transmitted across multiple generations

Abstract: It has been hypothesized that the effects of pollutants on phenotypes can be passed to subsequent generations through epigenetic inheritance, affecting populations long after the removal of a pollutant. But there is still little evidence that pollutants can induce persistent epigenetic effects in animals. Here, we show that low doses of commonly used pollutants induce genome‐wide differences in cytosine methylation in the freshwater crustacean Daphnia pulex. Uniclonal populations were either continually expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 102 publications
(253 reference statements)
0
15
0
Order By: Relevance
“…This implies that only a subset of methylation variants may differentiate among populations. DNA methylations can be induced by environmental variance as shown in fish, mammals, plants, birds and invertebrates (Bossdorf et al, 2008 ; Cropley et al, 2012 ; Harney et al, 2022 ; Heckwolf et al, 2019 ; Nätt et al, 2012 ), and are proposed to have the potential to modulate phenotypes in a plastic manner (Duncan et al, 2022 ; Flores et al, 2012 ; Gatzmann et al, 2018 ; Marshall et al, 2019 ). Furthermore, inducible DNA methylations can be transmitted across generations, which exposes them to evolutionary forces at least on short timescales (Cubas et al, 1999 ; Nätt et al, 2012 ; Riddle & Richards, 2002 ; Sutherland et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that only a subset of methylation variants may differentiate among populations. DNA methylations can be induced by environmental variance as shown in fish, mammals, plants, birds and invertebrates (Bossdorf et al, 2008 ; Cropley et al, 2012 ; Harney et al, 2022 ; Heckwolf et al, 2019 ; Nätt et al, 2012 ), and are proposed to have the potential to modulate phenotypes in a plastic manner (Duncan et al, 2022 ; Flores et al, 2012 ; Gatzmann et al, 2018 ; Marshall et al, 2019 ). Furthermore, inducible DNA methylations can be transmitted across generations, which exposes them to evolutionary forces at least on short timescales (Cubas et al, 1999 ; Nätt et al, 2012 ; Riddle & Richards, 2002 ; Sutherland et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the idea that variation in phenotypes may be mediated by environmentally induced changes in DNA methylation profiles, which may facilitate the ability of populations to cope with changes in local climatic conditions on a shorter timescale than that of adaptive genetic changes. Furthermore, studies have shown that epigenetic changes can be heritable and may persist across generations (Harney et al, 2022 ; Nätt et al, 2012 ; Riddle & Richards, 2002 ; Sutherland et al, 2000 ). Studies on how DNA methylation variation is structured across geographical locations and combining this with variation in environmental factors such as, for example, temperature and precipitation, can inform and substantiate hypotheses on the role of DNA methylation in generating locally advantageous phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Dixon and Matz (2022), gene-body DNA methylation does not appear to directly regulate gene expression in invertebrates. However, recent papers have suggested a role for DNA methylation in species evolution, whereby environmentally induced DNA methylation is directly heritable (Skinner and Nilsson, 2021; Harney et al ., 2022) and may produce adaptive phenotypes. Multiple studies in arthropods have indeed demonstrated heritability of DNA methylation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in arthropods have indeed demonstrated heritability of DNA methylation (e.g. Wang et al ., 2016; Yagound et al ., 2020) including environmentally induced DNA methylation (Harney et al ., 2022). Given that DNA methylation has also been shown to be linked to the underlying genotype in various insect species (Wang et al ., 2016; Marshall et al ., 2019; Yagound et al ., 2019, 2020; Wu et al ., 2020) we predicted that it may be enriched in certain codon positions in order to provide substrate for selection, not through directly altering gene expression levels but through its mutagenic effect on the underlying genome, which may then cause transcriptional variation.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies in animals and plants were run for 1–3 generations only [ 179 ]. Exceptions include some studies with water flea Daphnia pulex , nematode Caenorhabditis elegans , tale cress Arabidopsis thaliana and the unicellular green alga Chlamydomonas reinhardtii , which were run for 15, >20, 30 and ~200 generations, respectively [ 180 , 181 , 182 , 183 ]. New studies over many more generations are necessary to obtain a better picture.…”
Section: Ecological Implications Of Epigenetic Diversity For Genetica...mentioning
confidence: 99%